Survival After Out‐of‐Hospital Cardiac Arrest in Children - Jayaram, Natalie (J Am Heart Assoc, 2015)
BACKGROUND: Little is known about survival after out‐of‐hospital cardiac arrest (OHCA) in children. We examined whether OHCA survival in children differs by age, sex, and race, as well as recent survival trends. METHODS AND RESULTS: Within the prospective Cardiac Arrest Registry to Enhance Survival (CARES), we identified children (age <18 years) with an OHCA from October 2005 to December 2013. Survival to hospital discharge by age (categorized as infants [0 to 1 year], younger children [2 to 7 years], older children [8 to 12 years], and teenagers [13 to 17 years]), sex, and race was assessed using modified Poisson regression. Additionally, we assessed whether survival has improved over 3 time periods: 2005–2007, 2008–2010, and 2011–2013. Of 1980 children with an OHCA, 429 (21.7%) were infants, 952 (48.1%) younger children, 276 (13.9%) older children, and 323 (16.3%) teenagers. Fifty‐nine percent of the study population was male and 31.8% of black race. Overall, 162 (8.2%) children survived to hospital discharge. After multivariable adjustment, infants (rate ratio: 0.56; 95% CI: 0.35, 0.90) and younger children (rate ratio: 0.42; 95% CI: 0.27, 0.65) were less likely to survive compared with teenagers. In contrast, there were no differences in survival by sex or race. Finally, there were no temporal trends in survival across the study periods (P=0.21). CONCLUSIONS: In a large, national registry, we found no evidence for racial or sex differences in survival among children with OHCA, but survival was lower in younger age groups. Unlike in adults with OHCA, survival rates in children have not improved in recent years.